2022
DOI: 10.24084/repqj20.450
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost variable-speed wind turbines design by recycling small electrical machines. Arrangement of permanent magnets in the rotor

Abstract: This paper describes the design of low-cost variablespeed wind turbines by recycling small electrical machines. In this way, electrical machines such as automobile claw-pole alternators, induction motors for domestic applications, or simply electric motors for some industrial applications are studied, considering their reuse as permanent magnet synchronous generators (PMSG) in small wind turbines or hydro-power turbines. The main purpose is the integration of hybrid energy conversion systems (wind and hydrauli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Putting together (1), (4-6) and (14-17), the diameter-cubed sizing equation is obtained (18). Results are shown in Table III.…”
Section: B Diameter-cubed Sizing Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Putting together (1), (4-6) and (14-17), the diameter-cubed sizing equation is obtained (18). Results are shown in Table III.…”
Section: B Diameter-cubed Sizing Equationmentioning
confidence: 99%
“…In [17] the rotor of a claw-pole alternator is used together with a conventional stator to build a small PMSG for wind energy harvesting. It is shown that different PM arrangements on the rotor lead to different torques and efficiencies [18].…”
Section: Introductionmentioning
confidence: 99%